Antifungal Long-Chain Alkenyl Sulphates Isolated from Culture Broths of the Fungus Chaetopsina sp. - Crespo, Gloria; González-Menéndez, Víctor; de la Cruz, Mercedes; Martín, Jesús; Cautain, Bastien; Sánchez, Pilar; Pérez-Victoria, Ignacio; Vicente, Francisca; Genilloud, Olga; Reyes, Fernando (Planta Medica, 2017)
During a high-throughput screening program focused on the discovery and characterization of new antifungal compounds, a total of 8320 extracts from Fundacion MEDINAʼs collection were screened against a panel of 6 fungal parasitic strains, namely Candida glabrata, Candida krusei, Candida parapsilosis, Candida tropicalis, Candida albicans, and Aspergillus fumigatus. A total of 127 extracts displayed antifungal properties and, after LC/MS dereplication, 10 were selected for further fractionation. Bioassay-guided fractionation from a 1-L fermentation of one of these extracts, belonging to the fungus Chaetopsina sp., led to the isolation of linoleyl sulphate (1), linolenyl sulphate (2), and oleyl sulphate (3) as the compounds responsible for the antifungal activity. These molecules were previously described as synthetic products with the ability to produce the allosteric inhibition of soybean lipoxygenase and human lipoxygenase.
Keywords: long-chain sulphates; Chaetopsina sp.; Beilschmiedia tawa; antifungal; structural elucidation